Applying computational Materials Design (CMD) toward efficient hydrogen production from water - Muhida, Rifki; Rahman, Md. Mamudur; Muhida, Riza; Kasai, Hideaki (2010)
Hydrogen is probably the most promising solution to our global energy problems for the future. However, in order to support the developing hydrogen economy, efficient processes for hydrogen production and storage become necessary. Now a days, the hydrogen production is a large and growing industry. Globally, some 50 million metric tons of hydrogen are produced in a year. The growth rate is around 10% per year. Hydrogen can be produced using fossil fuels via steam reforming or partial oxidation of natural gas and by coal gasification. Produced in this fashion, hydrogen will generate less CO2 than conventional internal combustion engines (including the emissions during fuel production, delivery, and use in the vehicle), and thus contributes less to global warming. It can also be produced via electrolysis using electricity and water, consuming approximately 50 kilowatt hours of electricity per kilogram. This method is still expensive. The direct thermal splitting of water, 2H2O